Stands on globalization opinion paper / Manuel Denner - Manuel, Denner (Universiti Teknologi Mara, Selangor: Puncak Alam Campus, 2018)
In Jason Inch’s TED talk on Future Globalization is advising that companies need to understand their consumer base in a rapidly changing global business environment. It is clear for everybody that globalization plays one role in this change; however, there are a few variables that are forming the term of globalization, such as mass migration, geopolitical orientation, the Internet and its way of easing communication. Knowledge about cultural differences is a crucial thing and even more important than it was ever before. Therefore corporations are obliged to also take economic and political variables into account if they want to target t heir respective audience. Moreover, Inch says that companies should be ensured that cultural understanding needs to be trained as well as languages, knowledge about religion, values and “most importantly” about the culinary delights in a given country. Nowadays, it is about transcreating and not about translating when it comes to doing business on an international basis. “Transcreating” is important because of the fact that we are now living in an interconnected world where only translating would not be effective, you have to make things understandable for everybody. Inch also stipulates that cultural awareness is determining success or failure in today’s world. People should build bridges by having that kind of knowledge and not being afraid and run away be cause they have a lack in intercultural communication. In my opinion, Inch is right in what he is saying; everybody nowadays needs to have intercultural knowledge to drive business forward. It is not only a good asset to have intercultural knowledge; it is a necessity to have it.